RBM39 shapes innate immunity by controlling the expression of key factors of the interferon response - Li, Teng-Feng; Rothhaar, Paul; Lang, Arthur; Grünvogel, Oliver; Colasanti, Ombretta; Ugarte, Santa Mariela Olivera; Traut, Jannik; Piras, Antonio; Acosta-Rivero, Nelson; Gonçalves Magalhães, Vladimir; Springer, Emely; Betz, Andreas; et al. (Frontiers in Immunology, 2025)
Background and aimsThe contribution of innate immunity to clearance of viral infections of the liver, in particular sensing via Toll-like receptor 3 (TLR3), is incompletely understood. We aimed to identify the factors contributing to the TLR3 response in hepatocytes via CRISPR/Cas9 screening.MethodsA genome-wide CRISPR/Cas9 screen on the TLR3 pathway was performed in two liver-derived cell lines, followed by siRNA knockdown validation. SiRNA knockdown and indisulam treatment were used to study the role of RNA-binding motif protein 39 (RBM39) in innate immunity upon poly(I:C) or cytokine treatment and viral infections. Transcriptome, proteome, and alternative splicing were studied via RNA sequencing and mass spectrometry upon depletion of RBM39.ResultsOur CRISPR/Cas9 screen identified RBM39, which is highly expressed in hepatocytes, as an important regulator of the TLR3 pathway. Knockdown of RBM39 or treatment with indisulam, an aryl sulfonamide drug targeting RBM39 for proteasomal degradation, strongly reduced the induction of interferon-stimulated genes (ISGs) in response to double-stranded RNA (dsRNA) or viral infections. RNA sequencing (seq) and mass spectrometry identified that transcription and/or splicing of the key pathway components IRF3, RIG-I, and MDA5 were affected by RBM39 depletion, along with multiple other cellular processes identified previously. RBM39 knockdown further restrained type I and type III IFN pathways by reducing the expression of individual receptor subunits and STAT1/2. The function of RBM39 was furthermore not restricted to hepatocytes.ConclusionWe identified RBM39 as a regulatory factor of cell intrinsic innate immune signaling. Depletion of RBM39 impaired TLR3, RIG-I/MDA5, and IFN responses by affecting the basal expression of key pathway components.